Recyclable silver nanoplate-decorated copper membranes for solid-phase extraction coupled with surface-enhanced Raman scattering detection. Issue 11 (1st March 2018) - Yu, Xiaofei; Chang, Yuhong; Natarajan, Vinothkumar; Zhang, Xiaoli; Zhan, Jinhua
Abstract : Recyclable silver nanoplate-decorated copper membranes for solid-phase extraction coupled with surface-enhanced Raman scattering detection. Abstract : The development of solid phase extraction (SPE) combined with the sensitive detection of surface-enhanced Raman spectroscopy (SERS) has been successfully applied for the analysis of complex environmental samples. In this work, a silver nanoplate-decorated copper membrane was fabricated as a recyclable SERS-active SPE substrate. The membrane was fabricated via modified galvanic displacement on a commercial copper membrane. Compared with filter paper SERS substrates, the as-synthesized substrate has relatively rapid heat conduction, which can lead to a greater temporal stability under continuous laser irradiation conditions. The relative standard deviation (RSD) value of the intensity change is 0.31%. The experimental results also showed that these substrates have a long life and are reproducible even after 5 cycles. The RSD was calculated to be 12.13%, which indicates that this method was recyclable. The signal intensity of filtering is almost 28 times higher than that of the traditional dropping method, which proves that the membrane has rapid extraction ability. The qualitative and quantitative detection of phorate was investigated based on a flow-through method. A good linearity ( R 2 = 0.98) was achieved for phorate in the concentration range of 3.84 to 288 nmol L −1 . In addition, the simulated detection of phorate in actual water such as underground water, surface water, and drinking water was also studied. These results demonstrated its practical application to rapidly detect phorate in the real environment.